Integrating Maqāṣid al-Sharī‘ah and Sustainable Development Goals in Strengthening Waqf-Based Healthcare Initiatives in Muslim Communities - Kurniawan, Cecep Soleh; bin Mahmud, Hafini; Mohiddin, Hajah Mas Nooraini Binti Haji (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aimed to explore the significant role played by Islamic waqf in advancing healthcare services as part of the broader effort to achieve Sustainable Development Goals (SDGs) introduced by the United Nations, particularly SDG 3 on good health and well-being. The purpose of this exploration is simply to analyze how waqf functions as a sustainable financial mechanism in funding hospitals, supporting medical studies, and delivering essential health services to marginalized populations in Muslim communities. Adopting a descriptive-analytical methodology, this study draws on primary and secondary data sources, including waqf management reports, government publications, health policy documents, and peer-reviewed academic literature. Furthermore, case studies from Brunei Darussalam, Indonesia, Malaysia, and Turkey were used to show practical implementations of health-related waqf initiatives. The obtained results showed that waqf significantly contributed to addressing healthcare gaps, reducing inequality, and promoting equitable access to medical services. During the course of the investigation, Waqf institutions were found to embody Islamic principles of stewardship (istikhlāf) and reform (iṣlāḥ), offering a faith-based approach that corresponded with contemporary development frameworks. This study presents an original contribution through its integration of Islamic legal thought and global development paradigms, culminating in a conceptual model for health-waqf correspondence with SDGs targets. The obtained results showed that revitalizing health-focused waqf initiatives can strengthen public health systems in Muslim-majority communities, thereby providing an ethical, culturally resonant, and economically viable path toward sustainable development.